Los títeres y el lenguaje oral en niños de la Institución Educativa Inicial N°366 Rumococha, San Juan 2023 - Moreno Cardenas, Betty Priscilla (2024)
The main objective of this study was to determine the connection between the use of titles and speech progress in children enrolled in the Initial Educational Institution N°366 Rumococha, San Juan, during the year 2023. To fulfill this purpose, it was followed a relationship-centered approach and a non experimental, cross-sectional field research design was implemented with a focus on classification. The study population included all children enrolled in the institution. A complete sample of 110 participants was chosen to carry out the analysis. The methodology used involved observation, using an observation guide as a tool to collect data, which was then validated by experts in the field. Spearman's rating coefficients were applied to examine the relationship between the variables related to the use of titles and speech development in the children of the Institución Educativa Inicial N°366 Rumococha, San Juan, in the year 2023. Given that the p value was found to be greater than 0.05 (p > 0.05), the results indicate that there is no significant relationship between the use of titles and speech progress in children. According to these findings, with a compensation coefficient of 0.126, we can conclude that the association between both variables is of low magnitude.